The Dynamics of Ushul Fiqh in the Formulation of Contemporary Islamic Law: An Analysis of Istihsan, Maslahah Mursalah, 'Urf, and Sadd al-Zari'ah - AlFatih, Luthfi; Khadiah, Khadijah; Sari, Widya Sari (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study analyzes the dynamics of ushul fiqh in the formulation of contemporary Islamic law through an in-depth examination of four ijtihad methodologies: istihsan, maslahah mursalah, 'urf, and sadd al-zari'ah. The research employs a library research approach with content analysis methods applied to classical and contemporary ushul fiqh literature. Data is collected from primary sources, including classical ushul fiqh texts, and secondary sources such as relevant journals, books, and scholarly articles. The analysis is conducted descriptively-comparatively to identify the characteristics, applications, and relevance of each methodology in the context of contemporary Islamic law. The findings indicate that all four methods exhibit significant flexibility and applicability in addressing contemporary legal issues. Istihsan provides more just legal solutions through a substantive justice approach, maslahah mursalah allows for the formulation of laws based on public interests not explicitly mentioned in the texts, 'urf accommodates the social and cultural values of society, and sadd al-zari'ah serves as a preventive measure against potential harm. This research reveals that integrating these four methods within the framework of maqasid al-shari'ah can result in responsive, progressive legal rulings that remain rooted in the foundational principles of shari'ah. The study recommends the development of a methodological framework that integrates these four methods as an alternative solution to address the complexities of contemporary Islamic legal issues.